آثار الفساد المالى والإدارى وسبل مكافحته : حالة الجزائر - بو فاسة، سليمان Boufasah, Suleiman; بناصر، جبارة (الجمعية المصرية للاقتصاد السياسي والإحصاء والتشريع, 2014)
يتناول البحث ظاهرة الفساد المالي والإداري من خلال التعريف به وأسباب حدوثه والآثار الناجمة عنه، ثم الوسائل الممكنة لمكافحته، أي: ما هي السبل والإجراءات الكفيلة للحد من أثار الفساد المالي والإداري؟ واستعملنا المنهج الوصفي التحليلي، وافترضنا أن هناك عدة وسائل للحد من الظاهرة، لنخرج بنتيجة مفادها أن الفساد قد استفحل في الجزائر ولابد من إرادة قوية لدى المجتمع لتدعيم تلك الوسائل. Raised the financial and administrative corruption and ways to combat the case of Algeria - Research deals with the phenomenon of financial and administrative corruption through meta tags and whit occursandits effects, and possible means to combat it, what are the ways and measures to reduce the effects of financial and administrative corruption? And we used descriptive analytical method, and we assume that there are several ways to reduce the phenomenon onto come up with the conclusion that corruption has worsened in Algeria must be strong will to strengthen the community those means.
Keywords: الفساد المالى -- الفساد الإدارى -- مكافحة الفساد -- الجزائر